Fine‐grained azimuthal direction of arrival estimation using received signal strengths. Issue 10 (1st May 2017) - Maddio, S.; Cidronali, A.; Passafiume, M.; Collodi, G.; Maurri, S.
Abstract : We propose a direction of arrival (DoA) estimation technique, which is enabled by a single printed patch antenna capable of four reconfigurable beams at the operative frequency of 2.45 GHz. The direction of the messages sent by a nomadic wireless node is estimated and stored without the need of lengthy offline measurements, by correlating the real‐time received signal strength actual data and the expected antenna beams. The comparison is implemented with a least square technique with an extremely reduced computational cost. Experimental validations demonstrate the DoA estimation capability, with a mean error <2.3° with a variance of 1.9° within a domain of 90°.